Comparative efficacy of electrokinetic and static leaching for selective metal recovery and nutrient release from porphyry Cu tailings - Yujie Yan; Gawen R.T. Jenkin; Andrew P. Abbott; Alexandria Tanciongco; Carlo A. Arcilla; Cris Reven L. Gibaga; Daniel J. Smith; Djoan Kate Tungpalan; Jonathan E. Chambers; John Henry C. Gervasio; James Symons; Justine Perry T. Domingo; et al. (Chemical Engineering Journal, 2026)

Mid-season drain severity impacts on rice yields, greenhouse gas emissions and heavy metal uptake in grain: evidence from on-farm studies - Henry Perry; Daniela R. Carrijo; Aria H. Duncan; Scott Fendorf; Bruce A. Linquist (Field Crops Research, 2024)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

St. Helena: An Important Reproductive Habitat for Whale Sharks (Rhincodon typus) in the Central South Atlantic - Cameron T. Perry; Elizabeth Clingham; D. Harry Webb; Rafael de la Parra; Simon J. Pierce; Annalea Beard; LeeAnn Henry; Beth Taylor; Kenickie Andrews; Rhys Hobbs; Gonzalo Araujo; Alistair D. M. Dove (Frontiers in Marine Science, 2020)

Cytokinin activity during early kernel development corresponds positively with yield potential and later stage ABA accumulation in field-grown wheat (Triticum aestivum L.) - Hai Ngoc Nguyen; Laura Perry; Anna Kisiala; Henry Olechowski; R. J. Neil Emery (Planta, 2020)

The basis function approach for modeling autocorrelation in ecological data - Trevor J. Hefley; Kristin M. Broms; Brian M. Brost; Frances E. Buderman; Shannon L. Kay; Henry R. Scharf; John R. Tipton; Perry J. Williams; Mevin B. Hooten (Ecology, 2017)
Analyzing ecological data often requires modeling the autocorrelation created by spatial and temporal processes. Many seemingly disparate statistical methods used to account for autocorrelation can be expressed as regression models that include basis functions. Basis functions also enable ecologists to modify a wide range of existing ecological models in order to account for autocorrelation, which can improve inference and predictive accuracy. Furthermore, understanding the properties of basis functions is essential for evaluating the fit of spatial or time‐series models, detecting a hidden form of collinearity, and analyzing large data sets. We present important concepts and properties related to basis functions and illustrate several tools and techniques ecologists can use when modeling autocorrelation in ecological data.

Amphetamine increases activity but not exploration in humans and mice - Arpi Minassian; Jared W. Young; Zackary A. Cope; Brook L. Henry; Mark A. Geyer; William Perry (Psychopharmacology, 2016)

Identification and evaluation of quantitative trait loci underlying resistance to multiple HG types of soybean cyst nematode in soybean PI 437655 - Yongqing Jiao; Tri D. Vuong; Yan Liu; Clinton Meinhardt; Yang Liu; Trupti Joshi; Perry B. Cregan; Dong Xu; J. Grover Shannon; Henry T. Nguyen (Theoretical and Applied Genetics, 2015)

Effect of methamphetamine dependence on inhibitory deficits in a novel human open-field paradigm - Brook L. Henry; Arpi Minassian; Mandy van Rhenen; Jared W. Young; Mark A. Geyer; William Perry (Psychopharmacology, 2011)

QTL, additive and epistatic effects for SCN resistance in PI 437654 - Xiaolei Wu; Sean Blake; David A. Sleper; J. Grover Shannon; Perry Cregan; Henry T. Nguyen (Theoretical and Applied Genetics, 2009)

Increased metabolic cost of maintenance in hybrids of the stone crabs Menippe mercenaria and M. adina - C. A. Combs; R. P. Henry; T. M. Bert; H. M. Perry; M. West (Marine Biology, 1997)